WEGAN: a web-based community ecology platform - Sykes, Gina P.; Normington, Louisa; Poelzer, Jenna; Zhao, Shiyang; Allen, Dana; Stuart, Samuel; Oler, Eponine; Jot, Komal; Gautam, Vasuk; Zhao, Xin; Xia, Jianguo; Jickling, Glen C.; et al. (Frontiers in Ecology and Evolution, 2025)
Community ecology studies how species interact in their ecosystems, influenced by environmental and phenotypic factors. Analyzing these complex interactions requires specialized software or proficiency in statistical programming. While many stand-alone community ecology software tools exist, there is a gap for a free and widely available webserver to support community ecology analysis. To address this shortcoming we have developed WEGAN (Web-based Ecological Group Analysis), an easy-to-use webserver for analyzing and visualizing community ecology data. WEGAN is designed to provide features offered by popular programs such as vegan through a point-and-click web interface. Specifically, WEGAN provides a wide range of community ecology methods to support the analysis and visualization of trends in dispersal, diversity, and taxonomy as well as univariate and multivariate statistics for clustering, classification, correlation, and ordination analysis. WEGAN offers intuitive workflows and generates detailed tables, publication quality figures and a complete (reproducible) R coding history of all inputs, operations and outputs for every user session, together with comprehensive tutorials. WEGAN was developed to help with the teaching and training of community ecology and to encourage wider use of sophisticated community ecology techniques. WEGAN is freely available at https://www.wegan.ca.